2004
DOI: 10.1103/physrevlett.93.196601
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Transport in Polymer Nanofibers

Abstract: We report our transport studies in quasi one-dimensional (1D) conductors -helical polyacetylene fibers doped with iodine and the data analysis for other polymer single fibers and tubes. We found that at 30 K < T < 300 K the conductance and the current-voltage

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
128
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 26 publications
6
128
0
Order By: Relevance
“…The existence of two slopes at T > 30 K: namely ζ ~ 1.3 at low biases and ζ ~ 2.1 at high biases, can be attributed to the transition from the 2D tunneling in polymer nanoarray at low temperature to the quasi-1D Luttinger liquid-like transport at higher temperature, described in detail in Ref. 13, where V t ~ 0 and thus the Ohmic regime in I-Vs becomes available. This behavior correlates well with the crossover from Luttinger liquid to Coulomb blockade regime observed in MWNT recently [27,28].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of two slopes at T > 30 K: namely ζ ~ 1.3 at low biases and ζ ~ 2.1 at high biases, can be attributed to the transition from the 2D tunneling in polymer nanoarray at low temperature to the quasi-1D Luttinger liquid-like transport at higher temperature, described in detail in Ref. 13, where V t ~ 0 and thus the Ohmic regime in I-Vs becomes available. This behavior correlates well with the crossover from Luttinger liquid to Coulomb blockade regime observed in MWNT recently [27,28].…”
mentioning
confidence: 99%
“…In this connection polyacetylene (PA) nanofibers are of particular interest as the model system for nanotransport studies because of the simple chemical structure, well defined polycrystallinity [9], and good ability for doping [10][11][12]. It is shown that at temperature 30 K < T < 300 K doped polymer nanofibers demonstrate some transport features characteristic of quasi-1D systems, namely, series of Luttinger liquids separated by intra molecular barriers [13]. This implies the power-law behavior in both the temperature dependence of the conductance, G(T), and I-V characteristics, I(V) [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, progress in nanofabrication technologies has made it possible to manufacture a variety of single-and few-channel quantum wires connected to the electric leads and to perform systematic transport measurements on the very narrow wires. The latter include single-wall carbon nanotubes 8,9,10,11,12,13,14 , semiconductor-based 15,16,17,18 and metallic 19 quantum wires, polymer nanofibers 20 , as well as quantum Hall edge states. 21,22 The LL nature of these strongly correlated quantum wires has been supported by a wealth of experimental findings.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The LL nature of these strongly correlated quantum wires has been supported by a wealth of experimental findings. 8,9,10,11,12,13,14,15,16,19,20,21,22 Another class of strongly-correlated quantum wires that has recently attracted a lot of interest is ultracold atomic gases confined to 1D geometry, for review see Ref. 23.…”
Section: Introductionmentioning
confidence: 99%